2011
DOI: 10.1128/aac.00521-11
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Infections in Renal Transplant Recipients: Effect of Caspofungin on Polymorphonuclear Cells

Abstract: This study aimed to compare the caspofungin immunomodulating activities against Candida albicans on polymorphonuclear cells (PMNs) from renal transplant recipients (RTRs) and healthy subjects (HSs). RTR PMNs showed a significantly reduced fungicidal activity compared with that of HS PMNs. Addition of caspofungin to RTR PMNs significantly potentiated the yeast intracellular killing rate, achieving values similar to those observed for HS PMNs. These data show that caspofungin is suitable for invasive candidiasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our results [39,[44][45][46] confirm the literature data [41 ,47] according to which caspofungin (CAS) has immuneenhancing properties that influence human PMNs from both immmunocompetent and immunocompromised subjects against yeasts. In detail, CAS at various concentrations displays a positive interaction with healthy subject PMNs on intracellular killing activity through a direct action exerted on either C. albicans or PMNs [39].…”
Section: Antifungal Agentssupporting
confidence: 94%
See 1 more Smart Citation
“…Our results [39,[44][45][46] confirm the literature data [41 ,47] according to which caspofungin (CAS) has immuneenhancing properties that influence human PMNs from both immmunocompetent and immunocompromised subjects against yeasts. In detail, CAS at various concentrations displays a positive interaction with healthy subject PMNs on intracellular killing activity through a direct action exerted on either C. albicans or PMNs [39].…”
Section: Antifungal Agentssupporting
confidence: 94%
“…In detail, CAS at various concentrations displays a positive interaction with healthy subject PMNs on intracellular killing activity through a direct action exerted on either C. albicans or PMNs [39]. The most interesting result pertains CAS synergistic effect even on PMNs harvested from patients with renal dysfunction, such as RTRs and HDs: the addition of CAS to RTR and HD-PMNs potentiates the intracellular fungal killing rates against both C. albicans [44,45] and a multidrug resistant (MDR) C. glabrata [46], achieving values similar to those observed for healthy subjects. These data underline the CAS role in the total restoration of the impaired PMN functions in immunocompromised patients not only against susceptible yeast cells, but also even against the MDR ones (Table 3).…”
Section: Antifungal Agentsmentioning
confidence: 93%
“…Moreover, caspofungin and micafungin have been shown to prime the human neutrophil response to Aspergillus species hyphae by inducing exposure of β-glucan on the hyphal surface [39]. Finally, different investigators showed that caspofungin can enhance the activity of impaired neutrophils from renal transplant recipients against Candida species [40]. These effects on the host immune response have the potential to be significant in mixed infections, both by a nonspecific potentiation of innate immune effectors that can act against both bacteria and fungi and by increased exposure of mold and yeast hyphae to lymphoid cells, which could be impaired in some polymicrobial infections [41].…”
Section: The Role Of Antifungal Agents and Future Directionsmentioning
confidence: 99%